Western Pacific Surveillance and Response: a journal to reflect the needs of the Region - Takeshi Kasai; Emma Field (World Health Organization Regional Office for the Western Pacific, 2010)
The Western Pacific Surveillance and Response (WPSAR) Journal was established to encourage countries in the Western Pacific Region to share information on the surveillance of and response to public health events specific to this Region. An important step in surveillance is the dissemination of results to stakeholders, and, in the current international environment, public health events in one country may be of interest to the Region or even globally. In recent years many countries in the Western Pacific Region have increased capacity in surveillance and response through the Asia Pacific Strategy for Emerging Diseases to meet the core capacity requirements of the International Health Regulations (2005), also known as IHR (2005). There is now an opportunity to encourage sharing of information as a result of these improvements.